Implementasi Problem Based Learning untuk meningkatkan kemampuan literasi Sains dan High Thinking Skills Pembelajaran IPA SD - Yunitasari, Dukha; Arnyana, Ida Bagus Putu; Suastra, I Wayan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Scientific literacy and high order thinking skills are important characteristics of 21st century learning. This study aims to find theoretical arguments for problem- based learning constructs in increasing scientific literacy and high order thinking skills in elementary natural science. The study uses the literature review by linking scientific views on problem based-learning theories with context of scientific literacy and high order thinking skills. Several arguments were obtained that problem-based learning was introduced in five phases, namely finding problem; formulating problem solutions, conducting studies, compiling reports and reflecting. Finding problems encourages characters to experience real context directly so that students have an appreciation of a problem. Formulating a problem will give birth to high order thinking skills, because students learn to connect the causality of problems and the causes the problems. Conducting studies to educate students to be scientific, and not to understand the problem unilaterally. Compiling reports to educate students to think systematically with a deductive or inductive ways of thinking. Reflecting trains students to get used to re-checking scientific work steps before drawing conclusions.